The Assessment of Bank Efficiency and Profitability: Recent Evidence from the Turkish Banking Sector, 2008 - 2013 - Onder, Bostanci (2014)
The recent estimation techniques with a broad balanced panel dataset are used in this study to estimate bank efficiency and profitability. Within a two-stage framework, the Stochastic Frontier Analysis (SFA) is employed in the initial stage to estimate bank efficiency that also becomes an independent variable to a second stage where the determinants of bank profitability are explored. In the second stage, the Instrumental Variables/Generalized Method of Moments (IV/GMM) estimator is used to analyse how bank-specific characteristics, macroeconomic variables, and industry-specific factors affect the profitability of 22 commercial banks that operate in Turkey over the period of 2008 - 2013. In each stage, several interesting results are found. The results show that bank efficiency reflected the state of the banking sector during the study period, with a gap persisting between the best and worst performing banks. Furthermore, the profitability determinants vary quite widely across the different levels of significance, sign and size of the effect. The level of bank efficiency has thus an important impact on bank profitability.